Evaluation of steel frame structures with the response of seismic isolators - Beykzade, Mohammad; Baghchesaraei, Alireza; Baghchesaraei, Omid Reza (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
As science keeps evolving over time, new solutions are being put forward for reducing structural damage. One such solution is the use of seismic isolation systems. Seismic isolation systems reduce the response of structures to the force of earthquakes by reducing the input (force) acceleration when the natural period of the structure increases. Therefore, the use of seismic isolation systems is recommended in the analysis of diverse structures.
Keywords: seismic isolation system; dynamic analysis; seismic isolators; earthquake engineering; steel building; system izolacji sejsmicznej; analiza dynamiczna; izolatory sejsmiczne; trzęsienie ziemi; konstrukcje stalowe